Digital Protection of Ancient Buildings Based on BIM Simulation Technology - Jiarui Yang (Advances in Multimedia)
To improve the digital protection effect of ancient buildings, this study improves the space digital technology, combines the digital interpolation method to carry out the space digital simulation algorithm research, and combines the BIM simulation technology on the basis of the improved algorithm to carry out the digital protection processing of the ancient buildings. Moreover, this study starts from the actual situation to construct an intelligent digital protection system of ancient building. In addition, through the ancient building spatial data database, this study uses the visualization function and the powerful spatial analysis ability of GIS technology to design and research the digital protection system of ancient building. Through simulation research, it can be known that the digital protection system of ancient buildings based on BIM simulation technology proposed in this study has a good simulation effect and can provide reliable technical support for the protection and subsequent restoration of ancient buildings.